Probabilistic design factors for pipes used for hydrogen transport. (27th November 2020) - Kuk Mijim, J.; Pluvinage, G.; Capelle, J.; Azari, Z.; Benamara, M.
Abstract: Probabilistic design factors for pipes used for hydrogen transport are proposed for 3 locations: urban, peri-urban and rural areas. The used method involves a risk equation defined as the product of probability of leakage after failure, probability to have a gas flow greater than a prescribed value, probability of ignition, probability of lethal effects greater than a threshold value and probability of the presence of a person corrected by an environment factor and a risk reduction coefficient. The results obtained are less conservative than the deterministic values provided by ASME code. Highlights: Probabilistic design factors for pipes have been established. The used method involves a risk equation. This approach is based on assumption of a risk 10 −5 probability. The results obtained are less conservative than values provided by ASME code.